0484 Exposure to ionising radiation and risk of lymphoma subtypes: analysis of the epilymph results. (21st August 2017) - Cocco, Pierluigi; loi, Matteo; Zhi, Qi; Satta, G; Enna, Maris G; Becker, Nickolaus; Benavente, Yolanda; Sanjosé, Sylvia De; Foretova, Lenka; Staines, Anthony; Maynadié, Marc; Nieters, Alexander; et al.
Abstract : Introduction: The association between ionising radiation and risk of solid tumours and leukaemia is well established; however, the role of low dose radiation exposure in the aetiology of lymphoma is still uncertain. We investigated the role of occupational exposure to internal and external ionising radiation in the aetiology of lymphoma and its major subtypes. Methods: Between 1998 and 2004, 2348 cases and 2465 controls from six different European countries participated in the multicentre EpiLymph case-control study. A detailed occupational history was collected by questionnaire in all participants a coded using the ISCO68 occupational and NACE industrial coding systems. Based on the same coding systems, we developed a Job Exposure Matrix (JEM) to assess probability and intensity of exposure to internal and external ionising radiation. We used unconditional logistic regression to calculate Odds Ratios and their 95% Confidence Intervals for lymphoma and its major subtypes associated with the ionising radiation exposure metrics, adjusting by age, gender, education and country. Results: Risk of lymphoma overall did not show an association with exposure to radiation either internal or external. Risk of Diffuse Large B-Cell Lymphoma (DLBCL) was elevated and did show an upward trend with intensity of exposure to external radiation (Low Intensity OR=2.1, 95% CI=0.97–4.46 and High Intensity OR=2.5, 95% CI=1.21–5.08). We did not observe any risk increase associated with internal exposure to ionising radiation. Conclusions: Our results provide limited support to the relation between external sources of ionising radiation and risk of DLBCL. We cannot exclude the possibility of bias due to the multiple comparisons we made.